Cysteine-mediated green synthesis of copper sulphide nanoparticles: biocompatibility studies and characterization as counter electrodes - Saona, Luis A.; Campo Giraldo, Jessica L.; Anziani Ostuni, Giovanna.; Órdenes Aenishanslins, Nicolás.; Venegas, Felipe A.; Giordana, María F.; Díaz, Carlos; Isaacs, Mauricio; Bravo, Denisse; Pérez Donoso, José M. (MDPI, 2022)
A one-pot green method for aqueous synthesis of fluorescent copper sulphide nanoparticles (NPs) was developed. The reaction was carried out in borax–citrate buffer at physiological pH, 37 °C, aerobic conditions and using Cu (II) and the biological thiol cysteine. NPs exhibit green fluorescence with a peak at 520 nm when excited at 410 nm and an absorbance peak at 410 nm. A size between 8–12 nm was determined by dynamic light scattering and transmission electron microscopy. An interplanar atomic distance of (3.5 ± 0.1) Å and a hexagonal chalcocite crystalline structure (βCh) of Cu2S NPs were also determined (HR-TEM). Furthermore, FTIR analyses revealed a Cu-S bond and the presence of organic molecules on NPs. Regarding toxicity, fluorescent Cu2S NPs display high biocompatibility when tested in cell lines and bacterial strains. Electrocatalytic activity of Cu2S NPs as counter electrodes was evaluated, and the best value of charge transfer resistance (Rct) was obtained with FTO/Cu2S (four layers). Consequently, the performance of biomimetic Cu2S NPs as counter electrodes in photovoltaic devices constructed using different sensitizers (ruthenium dye or CdTe NPs) and electrolytes (S2−/Sn2− or I−/I3−) was successfully checked. Altogether, novel characteristics of copper sulfide NPs such as green, simple, and inexpensive production, spectroscopic properties, high biocompatibility, and particularly their electrochemical performance, validate its use in different biotechnological applications.
Keywords: Counter electrode; Cu2S NPs; Fluorescent nanoparticles; Green synthesis